Personal and Work-Related Factors Associated with Good Care for Institutionalized Older Adults - López, Javier (Int J Environ Res Public Health, 2021)
Despite efforts to promote good care, many institutionalized older adults (IOA) experience elevated neglectful conditions and reduced person-centered care approaches. Based on the job demand–control model, this study aimed to analyze the relationship between nursing home professionals’ personal and organizational factors and good care provided to institutionalized older people. Data was collected through a self-administered survey completed by 208 nursing home staff members. Three dimensions of personal factors (i.e., personal accomplishment, depersonalization, and negative old age stereotypes) were significant predictors of good care. Depersonalization and negative old age stereotypes were negatively associated with IOA, and both good care and personal accomplishment were positively associated with good care in nursing homes. Only one work-related factor (i.e., management support) was positively associated with good care. Personal factors may play a significant role in good care. Management support offers a promising mechanism to promote good care among nursing home professionals. The findings support the need to change the focus on entirely completing care tasks to providing good care of residents in nursing homes that promotes management support, personal accomplishment, personalization and positive old age consideration, attitudes, and behaviors. Policies and interventions should be developed to address in a more humanized way.